Response of broiler chickens to carica papaya and talinium triangulare leaf meal under normal and subnormal diets (2018)
The use of locally available and cheap feed ingredients has received particular attention as a viable alternative to the use of conventional feedstuffs in developing countries. Vegetable-based feeds are rich sources of essential plant amino acids, vitamins, minerals, and antioxidants. Further to the rich contents mentioned, it has been established that green vegetable leaves are cheap and abundant sources of protein because of their ability to synthesize amino acids from a wide range of available primary materials. The aim of this study was to investigate the response of broiler chickens to Carica papaya and Talinium triangulare under normal and subnormal diets. In this study, the effects of C. papayaleaf meal and T. triangulare chopped leaves were assessed on growth performance and haematological parameters of broiler chickens. Two hundred and seventy 1-d old Arbor acres broiler chicks were used for the study. Each treatment had 5.replicates with 6 birds per replicate. Normal diets and subnormal diets were compounded with varying amounts of ingredients. The test ingredients were supplied at the rate of 10% of the main diets. The design of the experiment was a completely randomized design. All the treatments with subnormal diets obtained higher feed intake than treatments with normal diets. Birds on subnormal diet mixed with C. papaya leaf meal (24.03%) obtained the highest packed cell volume. The haemoglobin concentrations followed a similar pattern. Normal diets compared with control for feed conversion ratio.